The status of women in palmyrene society through the development of their representations in sculpture During the Roman period - ALmalake, Haea; SHahod, Mekael (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The current study aims to shedding light on the status of The Palmyrene women and their role in the society during the prosperity of Palmyra in the Roman period by studying the most important examples of religious and funerary sculptures found in different parts of the ancient city of Palmyra and its surroundings According to a chronological sequence that deals with the development of the representation of the women during the first three centuries AD. The most important results of this study are that the development of women's representation in sculptures has been done according to three basic stages: the first stage was represented as housewife through the huge number of household attributes that accompanying her, The second stage was represented as a lady by showing her beauty and the elegance of her dress and jewelry, and finally the third stage that showed representations of rich women and independent in positions were specific to men for two centuries.